Directing foreign aid for basic education : taking account of political will - Kosack, Stephen (The Brookings Institution WashingtonUS, 2009)
Suggests that donors should take account, before they give aid, of whether the receipient country's government has the political will to improve primary education, because education aid works when a government already has that political will to improve its population's access to quality primary education.